DNA damage in a solution containing copper(II) ions and ascorbic acid: Effect of the presence of sulfite (Brazilian Journal of Pharmaceutical Sciences, 2022)
Some antioxidant compounds have a pro-oxidant effect in the presence of transition metal ions, due to the reduction of Mn+ to M(n-1)+ with simultaneous formation of free radicals, which then promote DNA damage. In the present study, we evaluated the pUC19 DNA damage in a solution containing Cu(II) and ascorbic acid (AA) or S(IV) saturated with air by agarose gel electrophoresis. Our results showed that this damage decreases if AA and S(IV) are simultaneously added. This study also illustrates the importance of Cu(II) in this process, as no DNA damage was observed when AA or S(IV) were present in the absence of this metallic ion. Our data showed that DNA preservation depends on the concentration of AA and S(IV) and occurs when the [S(IV)]:[AA] ratio ranges from 1:1 to 20:1. Absorbance measurements and thermodynamic data show that no reaction occurs between AA and S(IV) when this mixture (pH 5.5) is added to pUC-19 DNA. The presence of dissolved oxygen may be the cause of AA consumption in the mixture of these two antioxidants, which subsequently decreases DNA damage.